Combination of oral vancomycin and intra-colonic vancomycin: Successful treatment of complicated pseudomembranous colitis in a child patient. (March 2019) - Bozkurt, Hüseyin Sancar; Kara, Banu
The Clostridium difficile infection–related disease varies from mild diarrhoea to pseudomembranouscolitis. Although C. difficile infection is commonly considered to be a hospital-acquired infection, a significant number of cases are community acquired. Community-acquired C. difficile infection can exhibit itself as ileus or toxic megacolon. Severe C. difficile infection that is unresponsive to intravenous metronidazole therapy requires more aggressive medical management and even surgical intervention. We present our case results for which vancomycin was administered both orally and intra-colonically. With this method, we treated the community acquired C. difficile infection patient who was presented as ileus.